Syntheses of Silylene‐Bridged Thiophene‐Fused Cyclopentadienyl ansa‐Metallocene Complexes for Preparing High‐Performance Supported Catalyst - Jeong, Sun Mi; Park, Ju Yong; Hyun, Yong Bin; Baek, Jun Won; Kim, Hagjun; Yoon, Yeokwon; Chung, Sangchul; Lee, Junseong; Lee, Bun Yeoul (Catalysts, 2022)
We synthesized a series of Me2Si‐bridged ansa‐zirconocene complexes coordinated by thiophene‐fused cyclopentadienyl and fluorenyl ligands (Me2Si(2‐R1 ‐3‐R2 ‐4,5‐Me2C7S)(2,7‐ R32C13H6))ZrMe2 (R1 = Me or H, R2 = H or Me, R3 = H, tBu, or Cl) for the subsequent preparation of supported catalysts. We determined that the fluorenyl ligand adopts an ɳ3‐binding mode in 9 (R1 = Me, R2 = H, R3 = H) by X‐ray crystallography. Further, we synthesized a derivative 15 by substituting the fluorenyl ligand in 9 with a 2‐methyl‐4‐(4‐tert‐butylphenyl)indenyl ligand, derivatives 20 and 23 by substituting the Me2Si bridge in 12 (R1 = Me, R2 = H, R3 = tBu) and 15 with a tBuO(CH2)6(Me)Si bridge, and the dinuclear congener 26 by connecting two complexes with a –(Me)Si(CH2)6Si(Me)– spacer. The silica‐supported catalysts prepared using 12, 20, and 26 demonstrated up to two times higher productivity in ethylene/1‐hexene copolymerization than that prepared with conventional (THI)ZrCl2 (21-26 vs. 12 kg‐PE/g‐(supported catalyst)), producing polymers with comparable molecular weight (Mw, 330-370 vs. 300 kDa), at a higher 1‐hexene content (1.3 vs. 1.0 mol%) but a lower bulk density of polymer particles (0.35 vs. 0.42 g/mL).
Keywords: Ethylene polymerization; Metallocene catalyst; Supported catalyst; Thiophene‐fused cyclopentadienyl